Flame-retardant cross-linked PDOL gel electrolyte and preparation method and application thereof
By using flame retardant crosslinking PDOL gel electrolyte in lithium metal batteries, combining polyether crosslinking network and Elosite nanotubes to coat flame retardant, the low ionic conductivity and flammability problems of solid electrolyte are solved, and the problem of low ionic conductivity and flammability of solid electrolyte is achieved. High energy density and safe lithium metal battery.
Patent Information
- Application Number
- CN202411270500.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2024-12-13
AI Technical Summary
The existing solid electrolytes have low ionic conductivity, poor mechanical modulus, poor cycle stability and flammability at room temperature, resulting in safety hazards and energy density limitations of lithium metal batteries.
Flame retardant crosslinked PDOL gel electrolyte is used to provide lithium ion binding sites through polyether crosslinking network, and the flame retardant is coated in Elosite nanotubes to form a composite flame retardant to enhance the structural stability of the electrolyte and mechanical strength, inhibit the growth of lithium dendrites.
It achieves high ionic conductivity, excellent mechanical properties and good cycle stability, reduces the safety hazards and energy density limitations of the battery, and improves the electrode interface compatibility and flame retardant performance.
Smart Images

Figure CN119133593A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solid electrolytes, and in particular to a flame-retardant cross-linked PDOL gel electrolyte and a preparation method and application thereof. Background Art
[0002] Lithium metal batteries play an important role in improving the energy density of power batteries. However, the poor compatibility of traditional organic liquid electrolytes with lithium metal leads to the growth of lithium dendrites, short circuits inside the battery, and serious safety hazards such as thermal runaway, which greatly limits the development of high-performance lithium metal batteries.
[0003] In order to solve the above technical problems, the prior art proposes that solid electrolytes can fundamentally solve the safety problems caused by the volatility, leakage and combustion of traditional liquid electrolytes, while reducing mass and volume. Existing solid electrolytes mainly include all-solid polymer electrolytes and quasi-solid electrolytes. Among them, all-solid polymer electrolyte lithium batteries have great advantages in high safety, high energy density and long cycle life, but the development of all-solid electrolytes with high ionic conductivity and high mechanical strength at room temperature is currently very challenging. Quasi-solid electrolytes, namely gel polymer electrolytes, have become the most promising electrolyte materials in lithium metal batteries due to their advantages such as high ionic conductivity, good mechanical properties, light weight, flexibility, easy processing and low price. However, the current gel polymer electrolytes still have problems such as low ionic conductivity, poor mechanical modulus, and excessive electrode / electrolyte interface impedance in actual applications.
[0004] Therefore, developing gel polymer electrolytes with both high ionic conductivity and excellent mechanical properties at room temperature and proposing strategies to effectively inhibit the growth of lithium dendrites are the keys to achieving the practical application of high-safety, high-energy-density lithium metal batteries. Summary of the invention
[0005] In view of the problems of low ionic conductivity, low mechanical strength, poor cycle stability and flammability of solid electrolytes, the present invention provides a flame retardant cross-linked PDOL gel electrolyte and its preparation method and application. The present invention utilizes the advantage of the polyether cross-linked network to provide dense lithium ion binding sites to improve its ionic conductivity. At the same time, the DMMP coated in the halloysite nanotubes gives the electrolyte flame retardant properties. The "positive inside and negative outside" charge distribution structure of the halloysite nanotubes also promotes the dissociation of lithium salts and provides more free lithium ions. The entire system ensures fast ion transmission and alleviates the uneven deposition and structural deterioration of the electrode during repeated dissolution / deposition, thereby obtaining a solid electrolyte material with superior cycle stability and rate performance. The present invention is proposed after fully investigating and understanding the current industry needs and the bottlenecks of solid electrolyte materials. Its smooth development can not only provide a new design idea for the research of solid electrolyte materials for lithium metal batteries, but also provide necessary innovative technical support and theoretical support for exploring the development of polyether polymer electrolytes, which has important academic significance and practical value.
[0006] The flame-retardant cross-linked PDOL gel electrolyte and its preparation method and application are achieved by the following technical solutions:
[0007] The present invention takes into account that the gel electrolyte is a polymer electrolyte of a composite small molecule solvent, which is a gel state between liquid and solid. It combines the advantages of liquid electrolyte and solid electrolyte in terms of ionic conductivity and mechanical properties, can avoid leakage, reduce electrolyte flammability and have good interface contact performance. Therefore, the present invention attempts to provide a gel polymer electrolyte and construct a polymer with a cross-linked structure to increase the polymer matrix's retention capacity for liquid solvents, while enhancing the structural stability of the gel polymer electrolyte, inhibiting the growth of lithium metal negative electrode dendrites, and improving the cycle stability of the battery, thereby achieving coordination between fast ion transport and high mechanical strength.
[0008] The present invention takes into account that the commonly used gel electrolyte matrices such as polyethylene oxide, polymethyl methacrylate, polyacrylonitrile and other polymers will burn when exposed to flames due to their intrinsic flammability. At the same time, the alkyl free radicals RH·, hydrogen free radicals H· and hydroxyl free radicals OH· generated by decomposition maintain the combustion chain reaction, resulting in certain safety hazards. Therefore, the present invention proposes to introduce flame retardants to solve the safety hazards caused by the intrinsic flammability of the above-mentioned polymers. However, the inventors found in the process of exploration that the direct introduction of flame retardants will cause the flame retardants to decompose on the surface of the lithium negative electrode, and the deterioration products will produce a thicker SEI layer, which will lead to changes in the composition and morphology of the lithium metal negative electrode, thereby causing Li +The increase in the transmission energy barrier and the growth of lithium dendrites reduce the utilization rate of active lithium. Therefore, the present invention uses halloysite nanotubes as a modifier, and the flame retardant is coated by the halloysite nanotubes, that is, the flame retardant is filled in the cavity structure of the halloysite nanotubes to obtain a composite flame retardant, thereby effectively blocking the direct contact between the flame retardant molecules and the lithium metal negative electrode without reducing the ionic conductivity and mechanical properties of the polymer, inhibiting the interfacial side reactions, and achieving a balance between the flame retardant properties and the electrochemical stability of the gel polymer electrolyte. The obtained composite flame retardant is compounded with a polyether cross-linked network to obtain a flame-retardant cross-linked PDOL gel electrolyte for lithium metal batteries. The polyether cross-linked network can increase the liquid loading capacity of the entire gel electrolyte system and provide lithium ion transmission binding sites, thereby improving its ion conductivity. The flame-retardant cross-linked PDOL gel electrolyte of the present invention is specifically prepared by the following steps:
[0009] Step 1, preparation of composite flame retardant:
[0010] The flame retardant is filled into the cavity structure of the halloysite nanotube by a vacuum impregnation method to obtain a composite flame retardant.
[0011] It should be noted that, in order to ensure the flame retardant effect of the flame retardant, the flame retardant preferably used in the present invention is an organic phosphorus flame retardant. And in order to further ensure that the organic phosphorus flame retardant used has a good flame retardant effect, in some preferred embodiments of the present invention, the flame retardant used is one or more of dimethyl methyl phosphate, trimethyl phosphate and triethyl phosphate.
[0012] In order to ensure that the flame retardant can be filled into the cavity structure of the halloysite nanotubes by vacuum impregnation, in some preferred embodiments of the present invention, the following steps are specifically performed:
[0013] 1) Halloysite nanotubes and dimethyl methyl phosphate are uniformly dispersed in a vacuum bottle at a mass ratio of 1:20 to 30 to obtain a mixed solution.
[0014] 2) Ultrasonic treatment of the uniformly dispersed mixed solution for 0.5 h to 1.5 h to obtain a suspension. In order to ensure the ultrasonic effect, in some preferred embodiments of the present invention, the ultrasonic power of the ultrasonic treatment is 250 W to 350 W and the ultrasonic frequency is 35 kHz to 45 kHz.
[0015] 3) placing the suspension in a vacuum environment with a vacuum degree of ≤-3.0 MPa for 0.5 h to 1.5 h, and performing vacuum impregnation to allow dimethyl methyl phosphate to enter the cavity of the halloysite nanotube.
[0016] 4) Repeat the above step 3) at least 4 times, and then store the vacuum impregnated suspension at normal pressure for 4 to 6 days to allow dimethyl methyl phosphate to fully enter the cavity of the halloysite nanotube, that is, to achieve the encapsulation of dimethyl methyl phosphate in the cavity structure of the halloysite nanotube, thereby preventing the side reaction between dimethyl methyl phosphate and lithium. At the same time, the "positive inside and negative outside" charge distribution structure of the halloysite nanotube also promotes the dissociation of lithium salts, providing more free lithium ions, which is beneficial to the electrochemical kinetics of the system. More importantly, the low desolvation energy barrier exhibited by the electrolyte system can effectively ensure fast ion transport, alleviate the uneven deposition and structural deterioration of the electrode during repeated dissolution / deposition, and thus prolong the battery cycle stability.
[0017] 5) Centrifuging the suspension obtained in step 4) to remove excess dimethyl methyl phosphate, and then drying to obtain a flame retardant coated with halloysite, that is, a composite flame retardant. In some preferred embodiments of the present invention, the drying temperature is 55° C. to 65° C., and the drying time is 16 h to 32 h.
[0018] Step 2, preparation of precursor solution:
[0019] The supplementary lithium salt, the initiator lithium salt and the monomer are mixed evenly, and then, succinonitrile and the composite flame retardant are added and mixed evenly to obtain a precursor solution.
[0020] It should be noted that the present invention takes into account the water absorption of the electrolyte. When preparing the precursor solution, the present invention is carried out in a glove box filled with argon gas to make the oxygen and water concentrations less than 0.1 ppm, thereby achieving the purpose of inert drying.
[0021] The present invention takes into account the factors of lithium ion transmission and polymerization, and realizes the role of ion transmission in the polymer system by synergistically combining the supplementary lithium salt and the initiator lithium salt. In order to ensure that the above effect can be achieved, in some preferred embodiments of the present invention, the molar ratio of the supplementary lithium salt to the initiator lithium salt is 1:0.3-0.5.
[0022] In some preferred embodiments of the present invention, the supplementary lithium salt used is selected from one or both of lithium bis(trifluoromethanesulfonyl imide) and lithium bis(fluorosulfonyl imide).
[0023] In some preferred embodiments of the present invention, the initiator lithium salt is selected from one or more of lithium difluorooxalatoborate, lithium tetrafluoroborate, lithium hexafluorophosphate and lithium hexafluoroarsenate. In order to ensure controllable polymerization time, electrolyte stability and avoid other impurities, in some more preferred embodiments of the present invention, the initiator lithium salt is lithium difluorooxalatoborate.
[0024] In order to ensure that the supplementary lithium salt and the initiator lithium salt can fully polymerize with the monomer, in some preferred embodiments of the present invention, the monomer used is one or more of 1,3-dioxolane, trimethylolpropane triglycidyl ether and fluoroethylene carbonate, so that the monomer used is in a liquid state, which can not only participate in the polymerization reaction as a monomer of the subsequent polymerization reaction, but also the liquid state can improve the contact effect between the various components, thereby further improving the reaction efficiency of the polymerization reaction. And in order to further ensure that the solvent used can achieve in-situ ring-opening polymerization, in some preferred embodiments of the present invention, the monomer used in the present invention is a mixed solvent composed of 1,3-dioxolane, trimethylolpropane triglycidyl ether and fluoroethylene carbonate to achieve the purpose of in-situ polymerization. In order to ensure that the amount of the monomer used can fully react with the supplementary lithium salt and the initiator lithium salt, in some preferred embodiments of the present invention, the amount ratio of the monomer to the supplementary lithium salt is 0.8mL~1.2mL:1mol.
[0025] In some preferred embodiments of the present invention, the volume ratio of the mixture of 1,3-dioxolane and trimethylolpropane triglycidyl ether to fluoroethylene carbonate is 0.65-0.75:0.25-0.35, so as to achieve the purpose of maximizing the polymer loading amount.
[0026] The present invention takes into account the mechanical properties of the polymer. In the mixture of 1,3-dioxolane and trimethylolpropane triglycidyl ether, the volume ratio of 1,3-dioxolane to trimethylolpropane triglycidyl ether is 93-97:3-7.
[0027] The present invention takes into account that the polymer has certain crystallinity and flammability. In order to improve the flame retardant properties of the polymer, in some preferred embodiments of the present invention, succinonitrile is added according to 15wt% to 25wt% of the mass of the above-mentioned solvent, and the above-prepared composite flame retardant is added according to 5wt% to 15wt% of the mass of the above-mentioned solvent to achieve the purpose of plasticization and flame retardancy.
[0028] In order to ensure that the added succinonitrile and the composite flame retardant are fully mixed, in some preferred embodiments of the present invention, the mixture is mixed by stirring. For example, stirring for 6 hours to 18 hours can be regarded as mixing.
[0029] Step 3, heating treatment:
[0030] The precursor solution is injected into a polyethylene separator and subjected to a heating treatment so as to crosslink and polymerize the components in the precursor solution to obtain a flame-retardant crosslinked PDOL gel electrolyte.
[0031] The present invention takes into account the factors of avoiding contact between the positive and negative electrodes and absorbing the precursor solution, and uses a polyethylene separator as a polymer support layer to achieve the purpose of supporting isolation and absorbing liquid. In some preferred embodiments of the present invention, the thickness of the polyethylene separator used is 10μm to 15μm.
[0032] In order to ensure that the polyethylene diaphragm material can be effectively modified by injecting the precursor solution into the polyethylene diaphragm, in some preferred embodiments of the present invention, when the precursor solution is injected into the polyethylene diaphragm, the precursor solution is injected into the polyethylene diaphragm at a rate of 25 μL / cm 2 ~35μL / cm 2 The corresponding volume of precursor solution is injected into the polyethylene diaphragm using a pipette to avoid the situation where too little precursor solution is injected, resulting in insufficient electrolyte to maintain battery operation; at the same time, too much precursor solution is also avoided, resulting in exceeding the absorption range of the polyethylene diaphragm.
[0033] In order to facilitate the cross-linking and polymerization of the components in the precursor solution, the present invention preferably adopts a heating treatment method. And in order to ensure that the components in the precursor solution can be cross-linked and polymerized by heating treatment, in some preferred embodiments of the present invention, the temperature of the heating treatment is 55°C to 65°C, so that the lithium difluorooxalate borate in the precursor solution triggers the ring-opening polymerization reaction of the epoxy monomer at this temperature, that is, the ring-opening polymerization reaction of 1,3-dioxolane and trimethylolpropane triglycidyl ether forms a polyether cross-linked network, and then maintains small molecules such as fluoroethylene carbonate, succinonitrile and flame retardant that do not participate in the reaction in the polymer network to form a flame-retardant gel electrolyte. In other preferred embodiments of the present invention, heating is carried out at a temperature range of 55°C to 65°C for 12h to 36h to ensure sufficient cross-linking and polymerization.
[0034] The second object of the present invention is to provide a flame-retardant cross-linked PDOL gel electrolyte prepared by the above preparation method.
[0035] The third object of the present invention is to provide an application of the flame-retardant cross-linked PDOL gel electrolyte as an electrolyte material for a lithium metal battery.
[0036] Compared with the prior art, the present invention has the following beneficial effects:
[0037] The present invention breaks the game relationship mechanism among the electrochemical properties, mechanical properties and flame retardant properties of the polymer by performing a reasonable polymer composition structure design, thereby constructing a functionalized gel electrolyte having both electrochemical properties and mechanical strength.
[0038] The present invention uses cationic ring-opening in-situ polymerization to construct a cross-linked network with multi-functional cross-linking points, accurately controls the length of polymer segments and the number of polar functional groups to optimize the binding sites and binding forces between polymer molecules and solvent molecules, and obtains a gel polymer electrolyte with excellent mechanical strength and ionic conductivity. Further, through the "molecular locking" strategy, a flame retardant sustained-release structure is designed to optimize the chemical composition of the gel polymer electrolyte, increase the flame retardant properties of the polymer, and improve the electrolyte / electrode interface compatibility, thereby improving battery performance.
[0039] The invention uses epoxy small molecules that are easy to ring-open and multifunctional epoxy crosslinking agents as raw materials to obtain a polymer network, and prepares a flame-retardant crosslinked PDOL gel electrolyte by compounding with a multifunctional flame retardant. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 This is the infrared spectrum of the composite flame retardant D@H of Example 1.
[0041] Figure 2 TEM image and corresponding element distribution diagram of the composite flame retardant D@H of Example 1; Figure 2 In the figure, Figure a is a transmission electron microscope image of the composite flame retardant D@H of Example 1, Figure b is a high-angle annular dark field image of the composite flame retardant D@H of Example 1, Figure c is the element distribution map of oxygen in Figure b, Figure d is the element distribution map of silicon in Figure b, Figure e is the element distribution map of aluminum in Figure b, and Figure f is the element distribution map of phosphorus in Figure b.
[0042] Figure 3 This is the thermogravimetric curve of the composite flame retardant D@H in Example 1.
[0043] Figure 4 XRD spectra of PDOL, PDT and PDT-SF-D@H10.
[0044] Figure 5 Ionic conductivity test results of steel symmetric cells of PDOL, PDT, PDT-SF and PDT-SF-D@H10.
[0045] Figure 6 Electrochemical windows of steel / lithium batteries for PDOL, PDT, and PDT-SF-D@H10.
[0046] Figure 7 is the lithium ion migration number of the lithium symmetric battery of PDT-SF-D@H10.
[0047] Figure 8 This is the interface impedance diagram of the lithium symmetric battery of PDT-SF-D@H10 before and after 10mV polarization.
[0048] Fig. 9The lithium symmetric battery of PDT-SF-D@H10 is 0.1mAh·cm -2 @0.1mA·cm -2 Dissolution / deposition under
[0049] Fig.10 The cycling performance test results of LFP batteries of LE-D, PDT and PDT-SF-D@H10 at 2.0C.
[0050] Fig.11 The cycling performance test results of LFP batteries of LE-D, PDT and PDT-SF-D@H10 at 1.0C.
[0051] Fig.12 The rate performance test results of LFP batteries of LE-D, PDT and PDT-SF-D@H10.
[0052] Fig.13 The rate performance test results of NCM622 battery of PDT-SF-D@H10.
[0053] Fig.14 The cycling performance test results of NCM622 batteries of LE-D, PDT and PDT-SF-D@H10 at 0.2C.
[0054] Fig.15 The flame retardant performance test results of LE.
[0055] Fig.16 The flame retardant performance test results of PDT.
[0056] Fig.17 The flame retardant performance test results of PDT-SF-D@H10. DETAILED DESCRIPTION
[0057] The technical solutions in the embodiments of the present invention will be described clearly and completely below.
[0058] Example 1
[0059] This embodiment provides a flame retardant cross-linked PDOL gel electrolyte, which is prepared by the following steps:
[0060] Step 1, preparation of composite flame retardant:
[0061] 1) Halloysite nanotubes and dimethyl methyl phosphate are uniformly dispersed in a vacuum bottle at a mass ratio of 1:25 to obtain a mixed solution.
[0062] 2) The uniformly dispersed mixed solution was ultrasonically treated at an ultrasonic power of 300 W for 1 h to obtain a suspension.
[0063] 3) The suspension was placed in a vacuum environment of -3.0 MPa and allowed to stand for 1 hour, and dimethyl methyl phosphate was allowed to enter the cavity of the halloysite nanotubes by vacuum impregnation.
[0064] 4) Repeat the above step 3) 4 times, and then store the suspension at normal pressure for 5 days to allow DMMP to be fully coated.
[0065] 5) The suspension obtained in step 4) is centrifuged to remove excess dimethyl methyl phosphate, and then dried at 60° C. for 24 h to obtain a halloysite-coated DMMP flame retardant, denoted as D@H.
[0066] Step 2, preparation of precursor solution:
[0067] In a glove box filled with argon, oxygen and water concentration <0.1ppm, 1M lithium bistrifluoromethanesulfonyl imide and 0.4M lithium difluorooxalatoborate were fully dissolved in 0.7mL of a mixture of 1,3-dioxolane and trimethylolpropane triglycidyl ether in a volume ratio of 95%:5%, and 0.3mL of fluoroethylene carbonate. Succinonitrile and a composite flame retardant were added at a monomer ratio of 20wt% and 10wt%, respectively, and the precursor solution was obtained after stirring for 3h.
[0068] Step 3, heating treatment:
[0069] The precursor solution was injected into the PE separator and heated at 60 °C for 24 h to fully polymerize the precursor solution to obtain a flame-retardant cross-linked PDOL gel electrolyte, which was recorded as PDT-SF-D@H10.
[0070] Comparative Example 1
[0071] This comparative example provides a gel electrolyte, which is prepared by the following steps:
[0072] 1 M lithium bis(trifluoromethanesulfonyl)imide and 0.4 M lithium difluorooxalatoborate were mixed with 1 mL of 1,3-dioxolane and then heated at 60° C. for 24 h to obtain a gel electrolyte, which was labeled as PDOL.
[0073] That is, the difference between this comparative example and Example 1 is only that:
[0074] In this comparative example, trimethylolpropane triglycidyl ether, fluoroethylene carbonate, succinonitrile and composite flame retardant are not added.
[0075] Comparative Example 2
[0076] This comparative example provides a gel electrolyte, which is prepared by the following steps:
[0077] 1 M lithium bistrifluoromethanesulfonyl imide and 0.4 M lithium difluorooxalatoborate were fully dissolved in 0.7 mL of a mixture of 1,3-dioxolane and trimethylolpropane triglycidyl ether in a volume ratio of 95%:5%, and then heated at 60°C for 24 h to obtain a gel electrolyte, which was recorded as PDT.
[0078] That is, the difference between this comparative example and Example 1 is only that:
[0079] In this comparative example, no fluoroethylene carbonate, succinonitrile and composite flame retardant are added.
[0080] Comparative Example 3
[0081] This comparative example provides a gel electrolyte, which is prepared by the following steps:
[0082] Step 1, preparation of composite flame retardant:
[0083] 1) Halloysite nanotubes and dimethyl methyl phosphate are uniformly dispersed in a vacuum bottle at a mass ratio of 1:25 to obtain a mixed solution.
[0084] 2) The uniformly dispersed mixed solution was ultrasonically treated at an ultrasonic power of 300 W for 1 h to obtain a suspension.
[0085] 3) The suspension obtained in step 2) is centrifuged to remove excess dimethyl methyl phosphate, and then dried at 60° C. for 24 hours to obtain a composite flame retardant.
[0086] Step 2, preparation of precursor solution:
[0087] In a glove box filled with argon, oxygen and water concentration <0.1ppm, 1M lithium bistrifluoromethanesulfonyl imide and 0.4M lithium difluorooxalatoborate were fully dissolved in 0.7mL of a mixture of 1,3-dioxolane and trimethylolpropane triglycidyl ether in a volume ratio of 95%:5%, and 0.3mL of fluoroethylene carbonate. Succinonitrile and a composite flame retardant were added at a monomer ratio of 20wt% and 10wt%, respectively, and the precursor solution was obtained after stirring for 3h.
[0088] Step 3, heating treatment:
[0089] The precursor solution was injected into the PE separator and heated at 60°C for 24 h to fully polymerize the precursor solution to obtain a flame-retardant cross-linked PDOL gel electrolyte, which was recorded as PDT-SF-D&H10.
[0090] That is, the difference between this comparative example and Example 1 is only that:
[0091] The composite flame retardant in this comparative example was not subjected to vacuum impregnation treatment, but was prepared by a physical mixing method.
[0092] Comparative Example 4
[0093] This comparative example provides a gel electrolyte, which is prepared by the following steps:
[0094] 1 M lithium bistrifluoromethanesulfonyl imide, 10 wt % of dimethyl methylphosphonate by mass of 1,3-dioxolane and 1 mL of 1,3-dioxolane were mixed to obtain a gel electrolyte, which was recorded as LE-D.
[0095] Comparative Example 5
[0096] This comparative example provides a gel electrolyte, which is prepared by the following steps:
[0097] 1 M lithium bis(trifluoromethanesulfonyl)imide was mixed with 1 mL of 1,3-dioxolane to obtain a gel electrolyte, which was denoted as LE.
[0098] Experimental Section
[0099] (I) Infrared spectrum test
[0100] The present invention takes the composite flame retardant D@H, HNT and DMMP of Example 1 as an example, and performs infrared spectrum tests on them respectively, and the test results are as follows: Figure 1 shown.
[0101] Depend on Figure 1 It can be seen that compared with the FTIR spectrum of HNT, the FTIR spectrum of D@H at 1321 cm -1 The stretching vibration peak of the P=O group belonging to DMMP appeared at , which indicated the presence of DMMP in the D@H composite flame retardant, and to some extent explained that HNT successfully encapsulated DMMP.
[0102] (II) Transmission electron microscopy test and corresponding element distribution test
[0103] The present invention takes the composite flame retardant D@H of Example 1 as an example, and performs transmission electron microscopy test and corresponding element distribution test on it, and the test results are as follows: Figure 2 shown. Figure 2 In the figure, Figure a is a transmission electron microscope image of the composite flame retardant D@H of Example 1, Figure b is a high-angle annular dark field image of the composite flame retardant D@H of Example 1, Figure c is the element distribution map of oxygen in Figure b, Figure d is the element distribution map of silicon in Figure b, Figure e is the element distribution map of aluminum in Figure b, and Figure f is the element distribution map of phosphorus in Figure b.
[0104] And from Figure 2 It can be seen that the P element is evenly distributed in the HNT, which is a characteristic element of DMMP. This further proves that the present invention successfully encapsulates DMMP in the HNT.
[0105] (III) Thermogravimetric test
[0106] The present invention takes the composite flame retardant D@H of Example 1 as an example, and performs transmission electron microscopy test and corresponding element distribution test on it, and the test results are as follows: Figure 3 shown.
[0107] And by Figure 3 It can be seen from the thermogravimetric curve that the content of DMMP in the composite flame retardant D@H is about 23wt%.
[0108] (IV) XRD test
[0109] The present invention takes PDOL, PDT and PDT-SF-D@H10 as examples and performs XRD tests on them respectively. The test results are as follows: Figure 4 shown.
[0110] Depend on Figure 4 It can be seen that the peak shapes of PDOL and PDT are almost the same, but the diffraction peak intensity of PDT is lower and moves to a higher angle. Moreover, the diffraction peak almost disappears after the introduction of SN, FEC and D@H, indicating that the chain length of PDT generated by cross-linking DOL and TTE is longer and more disordered, the chain segments are closer together, and the crystallinity is lower. At the same time, the presence of additives and flame retardant fillers further reduces the crystallinity of the polymer.
[0111] (V) Electrochemical performance test
[0112] In the present invention, the PDT-SF-D@H10 of Example 1, the PDOL of Comparative Example 1, the PDT of Comparative Example 2, and the PDT-SF-D&H10 of Comparative Example 3 are assembled in the manner of steel sheet / electrolyte / steel sheet to obtain a CR2016 type coin battery, which is recorded as a steel symmetrical battery; in the manner of steel sheet / electrolyte / lithium sheet, a CR2016 type coin battery is assembled, which is recorded as a steel / lithium battery; in the manner of lithium sheet / electrolyte / lithium sheet, a CR2016 type coin battery is assembled, which is recorded as a lithium symmetrical battery; in the manner of lithium sheet / electrolyte / LFP positive electrode, a CR2016 type coin battery is assembled, which is recorded as an LFP battery; in the manner of lithium sheet / electrolyte / NCM622 positive electrode, a CR2016 type coin battery is assembled, which is recorded as an NCM622 battery. The following tests are performed on the CR2016 type coin battery.
[0113] 1) Ionic conductivity test
[0114] The present invention takes the steel symmetrical cells of PDOL, PDT, PDT-SF and PDT-SF-D@H10 as examples, and tests the ionic conductivity thereof respectively, and the test results are as follows: Figure 5 shown.
[0115] Depend on Figure 5 It can be seen that PDT-SF-D@H10 has the highest room temperature ionic conductivity, which is 1.51×10 -4 S cm -1 ; It also has the lowest activation energy, which is 0.108eV.
[0116] 2) Linear voltammetric test
[0117] The present invention takes PDOL, PDT and PDT-SF-D@H10 steel / lithium batteries as examples, and performs linear voltammetric tests on them respectively. The test results are as follows: Figure 6 shown.
[0118] Depend on Figure 6 It can be seen that the oxidation potential of PDT-SF-D@H10 is 4.7 V, the oxidation potential of PDOL is 4.2 V, and the oxidation potential of PDT is 4.1 V, that is, the oxidation potential of PDT-SF-D@H10 is much higher than that of PDOL and PDT, indicating that the PDT-SF-D@H10 electrolyte of the present invention has good oxidation stability compared with PDOL and PDT.
[0119] 3) Lithium ion migration number test
[0120] The present invention takes the lithium ion migration number of PDT-SF-D@H10 as an example, and the test results are as follows: Figure 7 shown.
[0121] Depend on Figure 7 It can be seen that PDT-SF-D@H10 has a very high lithium ion migration number t Li + =0.64.
[0122] 4) Interface impedance test
[0123] The present invention takes the lithium symmetric battery of PDT-SF-D@H10 as an example, and tests its interface impedance before and after 10mV polarization, and the test results are as follows Figure 8 shown.
[0124] Figure 8 The interface impedance diagram of the lithium symmetric battery of PDT-SF-D@H10 before and after 10mV polarization. It can be seen that PDT-SF-D@H10 has a smaller interface impedance of about 225Ω.
[0125] 5) At 0.1 mAh cm -2 Dissolution / deposition
[0126] The present invention takes the lithium symmetric battery PDT-SF-D@H10 as an example and studies its performance at 0.1 mAh·cm -2@0.1mA·cm -2 The dissolution / deposition under the conditions of Fig. 9 shown.
[0127] Depend on Fig. 9 It can be seen that the lithium symmetric battery assembled by PDT-SF-D@H10 maintains a stable voltage polarization within 2000 h with an overpotential of 47.7 mV and good interface compatibility.
[0128] 6) Cycling performance of LFP battery at 2.0C
[0129] The present invention takes LE-D, PDT and PDT-SF-D@H10 LFP batteries as examples, and tests their cycle performance at 2.0C respectively, and the test results are as follows Fig.10 shown.
[0130] Depend on Fig.10 It can be seen that the LFP battery assembled by PDT-SF-D@H10 reached 114.3 mAh g -1 The specific capacity of the battery is 85.6% after 500 cycles, which shows a considerable cycle life. Its cycle stability exceeds that of batteries using LE-D and PDT (the capacity decays sharply after 100 cycles, and the capacity retention rates are 65.4% and 31.2% respectively after 200 cycles).
[0131] 7) Cycling performance of LFP battery at 1.0C
[0132] The present invention takes LE-D, PDT and PDT-SF-D@H10 LFP batteries as examples, and tests their cycle performance at 1.0C respectively, and the test results are as follows Fig.11 shown.
[0133] Depend on Fig.11 It can be seen that the specific capacity of the LFP battery assembled with PDT-SF-D@H10 at 25°C and 1.0C is 118.7 mAh g -1 , the capacity retention rate after 900 cycles is 85.1%, and the average Coulombic efficiency is close to 100%. The specific capacity of the LFP battery of PDT and LE-D drops sharply after about 150 and 450 cycles, respectively, indicating that the PDT-SF-D@H10 electrolyte has a more stable long cycle life.
[0134] 8) Rate performance test of LFP battery
[0135] The present invention takes the LFP batteries of LE-D, PDT and PDT-SF-D@H10 as examples, and tests the LFP batteries thereof respectively, and the test results are as follows: Fig.12 shown.
[0136] Depend on Fig.12 It can be seen that the specific capacity of the LFP battery using PDT-SF-D@H10 at different rates at 25°C far exceeds that of the LFP battery using LE-D and PDT electrolytes, and has excellent rate performance.
[0137] 9) Rate performance test of NCM622 battery
[0138] The present invention takes the NCM622 battery of PDT-SF-D@H10 as an example, and tests its NCM622 battery, and the test results are as follows Fig.13 shown.
[0139] Depend on Fig.13 It can be seen that the NCM622 battery of PDT-SF-D@H10 has high specific capacity and symmetry at different rates at 25°C, and has good rate performance.
[0140] 10) Cycle performance test of NCM622 battery at 0.2C
[0141] The present invention takes LE-D, PDT and PDT-SF-D@H10 NCM622 batteries as examples, and tests their cycle performance at 0.2C respectively, and the test results are as follows Fig.14 shown.
[0142] Depend on Fig.14 It can be seen that the NCM622 battery of PDT-SF-D@H10 has a performance of 150.2 mAh g at 25 °C and 0.2C. -1 The high initial capacity of PDT-SF-D@H10 was achieved, and the capacity retention rate was 72.1% after 200 cycles. The specific capacities of NCM622 batteries of PDT and LE-D began to decrease at the beginning of the cycle, indicating that PDT-SF-D@H10 has excellent high-voltage tolerance.
[0143] Based on the above, the PDT-SF-D@H10 sample has a 1.51×10 -4 S / cm room temperature ionic conductivity, electrochemical window 4.7V, lithium ion migration number 0.64. Constant current charge and discharge test was carried out on NEWARE battery tester to obtain the cycle performance of the sample. The PDT-SF-D@H10 sample maintained good cycle stability and high specific capacity. The assembled Li / / LFP battery obtained 120mAh·g at a current density of 2.0C. -1 The specific capacity of the assembled Li / / NCM622 battery is about 150 mAh g at a current density of 0.2C. -1The specific capacity is about 200 cycles, and the capacity retention rate is greater than 70%. These indicate that the sample has great potential and advantages in obtaining a solid electrolyte material with good cycle stability.
[0144] (VI) Flame retardant properties
[0145] The present invention takes LE, PDT and PDT-SF-D@H10 as examples to test their flame retardant properties. The test results are as follows: Figure 15-17 shown.
[0146] Flame retardant performance test method: Test according to the flame test method in GB / T 8333-2022.
[0147] Fig.15 The flame retardant performance test results of LE show that LE burns violently immediately after encountering the flame, and burns completely and extinguishes after 4 seconds.
[0148] Fig.16 The flame retardant performance test results of PDT show that PDT burns strongly immediately after encountering flame, and burns completely and extinguishes in 3 seconds.
[0149] Fig.17 Figure 2 is the flame retardant test result of PDT-SF-D@H10. It can be seen that the PDT-SF-D@H10 electrolyte automatically extinguishes after contacting and leaving the flame. The self-extinguishing time is 2s, and the flame retardant effect is good.
[0150] Obviously, the above embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
Claims
1. A method for preparing a flame-retardant cross-linked PDOL gel electrolyte, characterized in that: The following steps are involved: The flame retardant is filled into the cavity structure of the halloysite nanotubes by a vacuum impregnation method to obtain a composite flame retardant; The flame retardant is an organophosphorus flame retardant; The supplementary lithium salt, the initiator lithium salt and the monomer are mixed, and then succinonitrile and the composite flame retardant are added and mixed to obtain a precursor solution; Injecting the precursor solution into a polyethylene separator and performing a heating treatment to crosslink and polymerize the components in the precursor solution to obtain a flame-retardant crosslinked PDOL gel electrolyte; The supplementary lithium salt is one or both of lithium bis(trifluoromethanesulfonyl imide) and lithium bis(fluorosulfonyl imide); The initiator lithium salt is one or more of lithium difluorooxalatoborate, lithium tetrafluoroborate, lithium hexafluorophosphate and lithium hexafluoroarsenate; The monomer is one or more of 1,3-dioxolane, trimethylolpropane triglycidyl ether and fluoroethylene carbonate.
2. The preparation method according to claim 1, characterized in that The flame retardant is one or more of dimethyl methylphosphonate, trimethyl phosphate and triethyl phosphate.
3. The preparation method according to claim 1, characterized in that: The molar ratio of the supplementary lithium salt to the initiator lithium salt is 1:0.3-0.
5.
4. The preparation method according to claim 1, characterized in that: The mass of the succinonitrile accounts for 15wt% to 25wt% of the monomer.
5. The preparation method according to claim 1, characterized in that: The mass of the composite flame retardant accounts for 5wt% to 15wt% of the monomer.
6. The preparation method according to claim 1, characterized in that: The mass ratio of the halloysite nanotubes to dimethyl methyl phosphate is 1:20-30.
7. The preparation method according to claim 1, characterized in that: The usage ratio of the monomer to the supplementary lithium salt is 0.8 mL to 1.2 mL: 1 mol.
8. The preparation method according to claim 1, characterized in that: The temperature of the heating treatment is 55°C to 65°C.
9. A flame-retardant cross-linked PDOL gel electrolyte prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the flame-retardant cross-linked PDOL gel electrolyte according to claim 9 as an electrolyte material for a lithium metal battery.
Citation Information
Cited By
Gel electrolyte and preparation method and application thereof
CN121097196A
